Coronary microvascular dysfunction in women: an overview of diagnostic strategies. (November 2013) - Kuruvilla, Sujith; Kramer, Christopher M
Coronary microvascular dysfunction (CMD) also known as syndrome X, is characterized by typical anginal symptoms, evidence of myocardial ischemia on non-invasive testing and normal to minimal coronary disease on coronary angiography. It has a female preponderance and has been detected in up to 50% of women presenting with chest pain symptoms. Definitive diagnosis of CMD is critical as recent evidence suggests that women with this condition are at increased risk of cardiovascular events in the future. Invasive coronary reactivity testing on coronary angiography is considered to be the 'gold standard' for diagnosis of CMD. Non-invasive imaging techniques such as PET and cardiac magnetic resonance hold promise for detection of CMD in the future.